ANALISIS MARKET SEGMENTATION, TARGETING, DAN POSITIONING TRANSPORTASI ONLINE GRAB DI KOTA BOGOR (STUDI KASUS PADA MAHASISWA UNIVERSITAS PAKUAN) - Herdiyana Herdiyana; Salmah Salmah (Universitas Pakuan, 2019)
This research aim is to find out the segmenting, targeting, and positioning on online transportation Grab in Bogor City by using Pakuan University students as the research sample. This research uses descriptive survey method to researches the phenomenon about online transportation service and learns various relevant aspects with segmenting, targeting and positioning. The population of the researhes is 14.138 student of Pakuan University and 389 students were taken as the sample. The sampling method uses probability sampling with proportional cluster sampling technique, the determination of the number of samples using the Slovin method. The results of this research shows the segmentation from online transportation Grab in Bogor City which is from West Bogor, used by most female, having home lifestyle, and having extrovert personality. The reason using Grab is for travelling and looking for convenience and paying the cheap price compared with the competitors. Grab users know that Grab having promos through Grab application. Loyalty Grab users are included in enough loyal category. Target market from Grab is selective specialization, on this market pattern, Grab enters a number of market segmentation by offering different products. And for this thing Grab enters segmentation as a transportation tool and also as goods delivery service. Grab positioning is to make their brand staying in consumer’s mind from usage side, which is as a transportation tool and service that provides convenience, comfort, safe, and fast.